Tax Rates, Tax Understanding, Tax Sanctions, Modernization of the Tax Administration System and Tax Socialization Increase Tax Compliance of MSMEs - Oliv Rosada Rizqi; Mulyanto Mulyanto; Retno Tri Handayani (Journal of Economics and Public Health, 2026)
This study aims to determine and analyze the influence of tax rates, tax understanding, tax sanctions, modernization of the tax administration system, and tax socialization on taxpayer compliance of MSMEs in Pati Regency. The research method used is quantitative. The sampling used in this study is by using the Accidental Sampling technique with a sample size of 100 respondents. The analysis method used is multiple linear regression, with tests carried out namely descriptive statistical tests, data normality tests, classical assumption tests, and hypothesis testing with the help of the SPSS 23 analysis program. The results of the study indicate that tax rates, tax understanding, tax sanctions, modernization of the tax administration system, and tax socialization have a positive and significant influence on taxpayer guarantees of MSMEs in Pati.